Heritage Management Models for Sustainable Community Tourism Development - Aušra Liorančaitė-Šukienė; Virginija Jurėnienė (Tourism and Hospitality)
Cultural heritage plays a critical role in sustaining community identity, particularly in the face of global economic and cultural shifts. This study explores models of heritage management, focusing on community-based tourism (CBT) as a vehicle for sustainable development. Using qualitative interviews with Lithuanian community representatives and a comparative analysis of global frameworks such as the AHC, ANZECC, and EU models, the paper highlights the importance of community engagement, grassroots initiatives, and collaborative governance. Findings reveal that while community-driven efforts can preserve cultural heritage and stimulate local economies, challenges such as limited funding, regulatory barriers, and stakeholder conflicts persist. Recommendations include formalizing organizational structures, leveraging international best practices, and fostering stronger community–government partnerships to balance cultural preservation and economic benefits.